Tax Literacy and Leadership Agility: Indigenous Peoples Awareness in Paying Taxes - Jamaluddin Ahmad; Hardianti Hardianti; Firmansya Firmansya; Hariyanti Hamid; Erfina Erfina (Indonesian Association for Public Administration (IAPA), 2020)
This study aims to identify and explain tax literacy and leadership agility at the awareness of indigenous peoples in paying taxes. Based on the report, land and building taxes' income is still low for the indigenous peoples of